The Doctor's, the Druggist's, and the Detail Rep's Dance: Who leads, who follows? - Rovers, J.P. (1991)
The author reviews some of the literature about interventions designed to influence physicians' prescribing patterns, particularly how the pharmacist and drug industry alter prescribing by primary care physicians. Many of the usual interventions are probably ineffective; a personal relationship with the physician is necessary to modify prescribing behavior consistently.